TERAPI KELUARGA VIRGINIA SATIR DALAM MENCEGAH PERCERAIAN - Ninil Elfira (Indonesian Journal of Counseling and Development, 2023)
Marriage is the union of two people, sometimes colored by problems ranging from simple to complex problems that lead to divorce. Many things are done so that problems do not arise in the household; one is by counseling with a family approach from Virginia Satir. The satirical model is a strengths-based approach that focuses on empowering human growth. This article will discuss in more detail the meaning of satire therapy in overcoming problems in the household, including a discussion of the meaning and goals of satire therapy in creating new experiences, the therapeutic framework, and the therapist's role so that it is believed to be able to overcome various problems that cause divorce in the household.